Experiences and perceptions of nurses and air ambulance service providers in carrying out aeromedical evacuations in Indonesia: A qualitative research - Ambarwati, Dwi; Warsini, Sri; Hapsara, Sunartini; Haryanti, Fitri (Belitung Raya Foundation, Indonesia, 2024)
Background: Basic non-military flight nurse training is essential for enhancing nurses’ competency in conducting aeromedical evacuations. Trained nurses possessing flight nurse proficiency are indispensable for ensuring stable patient conditions amidst the unique physical, physiological, and psychological challenges encountered during flights. Objective: This study aimed to describe the experiences and perceptions of nurses and air ambulance service providers regarding aeromedical evacuations. Methods: This study employed a qualitative descriptive design. Data were gathered from February to July 2023 through semi-structured online interviews with seven nurses and air ambulance service providers engaged in aeromedical evacuation. Content analysis was utilized to interpret the interview data. Results: Seven themes were generated: 1) Experiences in aeromedical evacuation experiences, 2) Challenges faced by nurses and air ambulance service providers during aeromedical evacuations, 3) Essential knowledge for nurses involved in aeromedical evacuations, 4) Efforts to improve nurses’ knowledge and skills, 5) Leveling of flight nurse training, 6) Flight nurse training methods, and 7) Flight nurse training evaluation strategies. Conclusion: Nurses and air ambulance service providers acknowledge the significant influence of the flight environment on changes in patient conditions during aeromedical evacuations. To effectively manage alterations in patient conditions during flights, healthcare workers equipped with aviation health competency are imperative. One approach to enhancing the competency of healthcare workers is through flight nurse training. The findings from this study serve as a valuable resource for policymakers and health-related institutions endeavoring to formulate aeromedical evacuation strategies.